Heels. The complete first season [videorecording (DVD)] - Waldron, Michael (Starz, 2022)
Two brothers and rivals, one a villain, or 'heel', in the ring; the other a hero, or 'face', war over their late father's wrestling promotion, vying for national attention in small-town Georgia.